Study on Spatio-temporal Variation Characteristics of Hydro-meteorological Factors in the Source Region of Yellow River - WANG Dong; WU Dongdong; JIE Xiaobai; LI Xuehui (Renmin Zhujiang)
In order to understand the variation characteristics of drought and flood in the sourceregion of Yellow River sufficiently, based on the hydro-meteorological data of the source regionof Yellow River from 1961 to 2016, this paper analyzes the trend, mutation and periodicity ofannual precipitation, annual average temperature and annual runoff by the the Mann-Kendall method,Pettitt test and Morlet wavelet analysis method, and studies the spatial variation characteristicsof annual precipitation and annual average temperature through the Kriging interpolation and spatialvariation coefficient. The results show that; for the annual precipitation,its rising trend isinsignificant, without significant mutation and with significant periodicity of 30 years;for theannual average temperature,its increasing trend is significant, with strong mutations around 1997and without significant periodicity;for the annual runoff,its decreasing trend is significant,with strong mutations around 1989 and significant periodicity of 30 years; the spatialdistribution difference of annual precipitation and average temperature are significant, withdecreasing trend for spatial distribution difference of annual precipitation and with obviousvariation trend for that of annual average temperature; before 2000, the spatial distributiondifference of annual average temperature was obvious, but that was even after 2000. The researchis helpful for understanding the evolution characteristics of water resources in river basin, which canserve as a technical reference for the water resource management.